2011
DOI: 10.1002/ece3.66
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genome sequence confirms distinctness of Australian and Asian wild rice

Abstract: Cultivated rice (Oryza sativa) is an AA genome Oryza species that was most likely domesticated from wild populations of O. rufipogon in Asia. O. rufipogon and O. meridionalis are the only AA genome species found within Australia and occur as widespread populations across northern Australia. The chloroplast genome sequence of O. rufipogon from Asia and Australia and O. meridionalis and O. australiensis (an Australian member of the genus very distant from O. sativa) was obtained by massively parallel sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 22 publications
13
80
0
Order By: Relevance
“…These taxa were identified within perennial populations previously referred to as O. rufipogon. Waters et al [167] focused on the chloroplast genome, using samples from just four individuals at a single site in each of Vietnam and northern Australia for O. rufipogon, and four individuals of O. meridionalis from a site in northern Australia. They found that the Australian O. rufipogon was more similar to the Australian O. meridionalis than it was to the Asian O. rufipogon.…”
Section: Wild Rice-an Invaluable Genetic Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…These taxa were identified within perennial populations previously referred to as O. rufipogon. Waters et al [167] focused on the chloroplast genome, using samples from just four individuals at a single site in each of Vietnam and northern Australia for O. rufipogon, and four individuals of O. meridionalis from a site in northern Australia. They found that the Australian O. rufipogon was more similar to the Australian O. meridionalis than it was to the Asian O. rufipogon.…”
Section: Wild Rice-an Invaluable Genetic Resourcementioning
confidence: 99%
“…Recent work on these under-researched and possibly under-valued northern Australian populations of native Oryza have revealed new taxa [166][167][168]. These taxa were identified within perennial populations previously referred to as O. rufipogon.…”
Section: Wild Rice-an Invaluable Genetic Resourcementioning
confidence: 99%
“…Recent investigations of large and widespread wild populations in tropical Australia (Henry et al ., 2010) suggest the presence of two distinct and possibly novel perennial wild A genome taxa [Figure 1; Waters et al . (2012); Sotowa et al . (2013); Brozynska et al .…”
Section: Introductionmentioning
confidence: 99%
“…Results also confirmed the distinctness of Asian and Australian wild rice relatives (Nock et al 2011;Waters et al 2012). This approach proved to be valid for phylogeny of closely related species and was subsequently used to resolve the entire AA genome rice species tree with addition of African and South American species (Wambugu et al 2015).…”
Section: Phylogeny Of Genus Oryzasupporting
confidence: 54%